Human B Cells Engage the NCK/PI3K/RAC1 Axis to Internalize Large Particles via the IgM-BCR - Verstegen, Niels J. M.; Unger, Peter-Paul A.; Walker, Julia Z.; Nicolet, Benoit P.; Jorritsma, Tineke; van Rijssel, Jos; Spaapen, Robbert M.; de Wit, Jelle; van Buul, Jaap D.; ten Brinke, Anja; van Ham, S. Marieke (Frontiers in Immunology, 2019)
Growing evidence indicate that large antigen-containing particles induce potent T cell-dependent high-affinity antibody responses. These responses require large particle internalization after recognition by the B cell receptor (BCR) on B cells. However, the molecular mechanisms governing BCR-mediated internalization remain unclear. Here we use a high-throughput quantitative image analysis approach to discriminate between B cell particle binding and internalization. We systematically show, using small molecule inhibitors, that human B cells require a SYK-dependent IgM-BCR signaling transduction via PI3K to efficiently internalize large anti-IgM-coated particles. IgM-BCR-mediated activation of PI3K involves both the adaptor protein NCK and the co-receptor CD19. Interestingly, we here reveal a strong NCK-dependence without profound requirement of the co-receptor CD19 in B cell responses to large particles. Furthermore, we demonstrate that the IgM-BCR/NCK signaling event facilitates RAC1 activation to promote actin cytoskeleton remodeling necessary for particle engulfment. Thus, we establish NCK/PI3K/RAC1 as an attractive IgM-BCR signaling axis for biological intervention to prevent undesired antibody responses to large particles.